Bridging academic and practice: A project-based learning approach to prepare university students to be future-ready - PAN, Gary (Institutional Knowledge at Singapore Management University, 2021)
Forces such as globalisation and digitalisation have led to profound changes in the business environment. Knowledge and skills needed for this VUCA world are evolving rapidly and drastically. Domain knowledge and technical skills need to be complemented by deep understanding of the business context. Apart from domain and interdisciplinary knowledge, university graduates today also need to equip themselves with a range of other skills that will allow them to thrive in the economic of tomorrow. Critical thinking and communication skills are likely to become increasingly important with more collaborations between and within organisations. in addition to skills, graduates may need to adopt new ways of thinking and develop innovative problem-solving capabilities.